Lady Gregory and Irish National Theatre Art, Drama, Politics - Remport, Eglantina (Bernard Shaw and His Contemporaries, 2018)
This book is the first comprehensive critical assessment of the aesthetic and social ideals of Lady Augusta Gregory, founder, patron, director, and dramatist of the Abbey Theatre in Dublin. It elaborates on her distinctive vision of the social role of a National Theatre in Ireland, especially in relation to the various reform movements of her age: the Pre-Raphaelite Movement, the Co-operative Movement, and the Home Industries Movement. It illustrates the impact of John Ruskin on the aesthetic and social ideals of Lady Gregory and her circle that included Horace Plunkett, George Russell, John Millington Synge, William Butler Yeats, and George Bernard Shaw. All of these friends visited the celebrated Gregory residence of Coole Park in Country Galway, most famously Yeats. The study thus provides a pioneering evaluation of Ruskin's immense influence on artistic, social, and political discourse in Ireland in the late nineteenth and early twentieth century.